The Roles of the Mangroves on the Bioaccumulation and Citogenotoxic Effects of Heavy Metals and Pesticides in the Food Web of a Tropical System - Gonzalez, Lucia Ivorra (University of Saint Joseph, 2020)
Mangroves are a unique group of plants, which offer a great variety of goods and services to the ecosystem and to the society. Regrettably, they have been globally threatened by urbanization and industrialization, among others, triggering overexploitation of the world’s mangrove forests despite their ecological and economic importance. As a result, mangroves are often under pollution stress as sinks or receivers for numerous man-made pollutants such as pesticides, which are the main focus of this thesis. One of the most widely applied chemicals in the word are the organochlorine pesticides (OCPs) that even after their supposedly worldwide ban between 1950s-1990s, they can still be detected in the environment. Numerous studies have been done in phytoremediation of pollutants by mangroves, but little attention has been given to the role of mangroves in the remediation of OCPs. For this reason, part of this thesis will focus on the occurrence and distribution of OCPs in intertidal tropical and sub-tropical areas around the world with and without mangroves. As a first goal (I), we evaluate —in a theoretical way— if the presence of mangroves affects or modifies the levels of OCPs in the surrounding environment. For this purpose, data from different matrices, such as water, sediment, benthic fauna and plants were included and discussed in this work. Moreover, and considering Macao’s location, we also quantified OCPs from surface waters of this region from areas with and without mangroves and included in this task. Besides this theoretical approach, this thesis also included some laboratoy and field work specifically focused on dicofol and 4,4’-dichlorobenzophenone (4,4’-DCBP, its main metabolite). Dicofol is an OCP strongly related to dichlorodiphenyltrichloroethane (DDT), which has been extensively used in China and more specifically, in the Pearl River Delta (PRD), a region under anthropogenic pressure. However, due to dicofol’s instability (i.e., sensitive to low pH, light exposure and high temperature), we expected to quantify 4,4′-DCBP (which is also common to DDT) as the main form present in the environment. As a second goal (II), we conducted a monitoring study in surface waters from Macao and Hong Kong, to evaluate the contamination status and water quality of these regions. Concentrations of 4,4’-DCBP, nutrients and physicochemical parameters were measured during transition and wet season, and at high and low tide. In addition, since the toxicity of this metabolite was totally unknown, we assessed it via two biological models: Daphnia magna and Artemia salina. Since 4,4’-DCBP was detected and quantified in both regions (2.8-30.0 ng/L), this thesis also includes experimental work focused on the assimilation and depuration pattern by a marine organism. For that purpose and as a final goal (III), we selected the common edible bivalve Meretrix as a model to evaluate the dynamics of accumulation and depuration of the pesticide dicofol. The Vietnamese clams were exposed during 15 days under two different concentrations of dicofol, and decontaminated for the same period of time. Quantification of 4,4’-DCBP was done during both phases (uptake and depuration) and at different sampling times. In summary, all these different works helped us to conclude that: I.1) As expected, vegetated areas with mangroves presented lower concentrations of OCPs for all the matrices, and also better quality in terms of pesticide pollution for water and sediments. Results obtained from Macao’s waters also revealed the same pattern, with mangroves areas having lower levels of contamination. Although the gathered data presented methodological variability (i.e. different quantification methods, extraction protocols, equipment used), the same pattern was observed among matrices, showing how robust and solid the results herein obtained are. II.1). Hong Kong presented higher concentrations of 4,4’-DCBP than Macao, which may be due to the use of dicofol as a pesticide and the use of antifouling-paint for ships. Moreover, concentrations of 4,4’-DCBP during wet season were below limits of quantification, demonstrating a seasonal pattern and a dilution effect due to higher river discharges during this period. II.2). Both regions showed possible eutrophication problems due to the high nutrient concentrations. These levels presented also a seasonal variability, with dissolved inorganic nitrogen and total dissolved solids higher during transition; and dissolved inorganic phosphorous, total suspended solids and chlorophyll a higher during wet season. II.3). Toxicity of 4,4’-DCBP was lower than the parent compound dicofol, and the levels quantified indicated a low environmental risk. However, it is important to pay attention to this compound since interaction with other contaminants could enhance their toxicity, or processes such as biomagnification or bioaccumulation could make low concentrations a threat for the environment. III.1). Different concentrations of dicofol presented different uptake and depuration kinetics. Animals exposed to higher concentrations (500 ng/L), had levels above limits of quantification (LOQ) after 24h exposure, unlike the ones exposed to lower concentrations (50 ng/L), which had levels <LOQ after the same period. The first ones also, presented lower uptake rates, and this could indicate that high dicofol concentrations in the system could affect the respiration rates of the organism. In addition, this work also showed that animals exposed to high concentrations of dicofol will need more than 15 days to depurate in order to reach safe levels for human consumption. The compilation of the work done in this thesis allowed us to better understand the role of mangroves ecosystems on the accumulation of OCPs and to provide solid information that could create strategies for mangroves management and conservation. Moreover, and as a first attempt, we were able to quantify this pesticide metabolite in the PRD (one of the most seriously contaminated areas in China), to determine its toxicity and to define its kinetics in an important organism such as the edible bivalve M. meretrix. We intend that this thesis will be helpful for the scientific community providing new insights regarding metabolite interactions (within and with other molecules) and toxicity (LC50 and theoretical risk assessment), which were unknown until now
Keywords: Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph